Respuesta :
a = Sock's weight
b = Princess' weight
c = Luna's weight
a : b = 4 : 5
b : c = 6 : 7
at this point, we have to change the 2 ratios (a : b and b : c) into one ratio (a : b : c)
to do that, we have to change the ratio number so the number b in both ratio is the same
a : b = 4 : 5 = 24 : 30
b : c = 6 : 7 = 30 : 35
From that we can conclude that
a : b : c = 24 : 30 : 35
Since we're looking for the ratio of Sock's weight to Luna's weight, it will be
a : c = 24 : 35
b = Princess' weight
c = Luna's weight
a : b = 4 : 5
b : c = 6 : 7
at this point, we have to change the 2 ratios (a : b and b : c) into one ratio (a : b : c)
to do that, we have to change the ratio number so the number b in both ratio is the same
a : b = 4 : 5 = 24 : 30
b : c = 6 : 7 = 30 : 35
From that we can conclude that
a : b : c = 24 : 30 : 35
Since we're looking for the ratio of Sock's weight to Luna's weight, it will be
a : c = 24 : 35
4:7 because 4 is sock's waeight and it says that in the first ratio and 7 is luna's weight because it says that in the last ratio